GROUNDED THEORY APPROACH : EMPLOYEE PERCEPTIONS OF SOCIAL MEDIA TO SUPPORT WORK PRODUCTIVITY - Raden Maart Adi Waskita Tjahjono; Jerry Heikal (PT. Media Akademik Publisher, 2024)
Social media has become an important part of people's lives, including employees in the workplace. This research aims to examine employee perceptions regarding the influencing factors of social media to support work productivity. This research uses a Grounded Theory approach with in-depth interview methods with 5 employees at a private company in Jakarta. The research population is employees at the company, while the research sample is 5 employees selected purposively. The research results show that there are three factors influencing social media to support work productivity, namely motivation factors, information factors and interaction factors. Motivational factors include motivation to work better, motivation to learn new things, and motivation to socialize with coworkers. Motivation to work better is influenced by information obtained from social media, while motivation to learn new things and socialize with colleagues is influenced by interactions carried out via social media. Information factors include faster and more accurate access to information, and ease of communicating with colleagues. Faster and more accurate access to information can increase employee work productivity, while ease in communicating with colleagues can increase employee collaboration and creativity. Interaction factors include increased collaboration between employees, and increased creativity and innovation. Increasing collaboration between employees can increase work productivity, while increasing creativity and innovation can improve the quality of employee work. The results of this research can be used by organizations to develop strategies for effective use of social media to increase employee work productivity.